Energy efficiency of agricultural systems in the southwest coastal zone of Bangladesh. (March 2019) - Talukder, Byomkesh; vanLoon, Gary W.; Hipel, Keith W.
Highlights: Agriculture is vital for long-term sustainability in coastal Bangladesh. Energy-efficiency indicators are used to evaluate different agricultural systems. CO2 emissions from coastal agriculture systems are assessed. Integrated agricultural systems are more energy-efficient and emit less CO2 . Policy makers and farmers can adopt the findings to ensure coastal sustainability. Abstract: Indicators for energy-use efficiency and levels of CO2 emissions were used to evaluate and compare a range of agricultural systems in coastal Bangladesh in order to identify the most energy efficient system. Using data collected by the authors, five different food production systems involving both agriculture and aquaculture in the coastal area of Bangladesh were studied. In particular, Bagda (shrimp), Bagda -rice, rice, Galda (prawn)-rice-vegetable, and traditional practice-based agricultural systems were thoroughly investigated. The findings revealed that the Galda (prawn)-rice-vegetable-based integrated agricultural system was the most energy-efficient system and released less CO2 than the other four systems.